Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1182/blood-2016-07-730564
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical hematopoietic transplantation for the cure of leukemia: from its biology to clinical translation

Abstract: The present review describes the biology of human leukocyte antigen haplotype mismatched ("haploidentical") transplantation, its translation to clinical practice to cure leukemia, and the results of current transplantation protocols. The 1990s saw what had been major drawbacks of haploidentical transplantation, ie, very strong host-versus-graft and graft-versus-host alloresponses, which led respectively to rejection and graft-versus-host disease (GVHD), being overcome through transplantation of a "mega-dose" o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 99 publications
3
42
0
Order By: Relevance
“…HaploHCT has the potential to fill a substantial therapeutic gap for these patients without a matched related or unrelated donor. Several retrospective studies have compared haploHCT to HLA‐matched allogeneic HCT for de novo AML but not in sAML …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HaploHCT has the potential to fill a substantial therapeutic gap for these patients without a matched related or unrelated donor. Several retrospective studies have compared haploHCT to HLA‐matched allogeneic HCT for de novo AML but not in sAML …”
Section: Discussionmentioning
confidence: 99%
“…Initial experiences with haploHCT in the 1990s resulted in poor outcomes due to T‐cell alloreactivity secondary to HLA‐mismatches with delayed engraftment, graft failures, and relatively high incidences of acute GVHD . Several strategies were developed to overcome these challenges, including ex vivo and in vivo TCD as well as T‐cell replete (TCR) grafts .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In order to remove T cells, responsible for graft-versus-host disease (GVHD), and B cells, from which posttransplant lymphoproliferative disease (PTLD) can arise, 4 positive selection of CD34 1 hematopoietic stem cells (HSCs) has been employed for many years in haplo-HSCT. [1][2][3] Although the administration of CD34…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the anticancer efficacy of NK cells comes from allogeneic or haploidentical hematopoietic stem cell (HSC) transplantations that have been used in combination with chemotherapy in the treatment of different forms of leukemia (9). This has shown that NK cells formed from the transplant not only are efficient in killing of allogeneic leukemia cells but are also instrumental in reducing the incidence of graft versus host disease due to their killing activity for dendritic cells (10).…”
Section: Introductionmentioning
confidence: 99%